rBCG-LTAK63 enhances protection against tuberculosis by inducing autophagy and circadian gene regulation - Marques-Neto, Lázaro M.; Trentini, Monalisa M.; Moreno, Ana Carolina R.; Eto, Silas F.; Carvalho, Ana Carolina O.; Neto, Almiro P.S.; Amaral, Murilo S.; Martins, André G. C.; Gonçalves, André N. A.; Chudzinski-Tavassi, Ana Marisa; Kanno, Alex I.; Tagliabue, Aldo; et al. (Frontiers in Immunology, 2025)
Tuberculosis (TB) remains a global public health challenge, with the current BCG vaccine providing limited efficacy in adults, and available treatments being lengthy and debilitating. To overcome these challenges, we have previously developed a recombinant BCG strain expressing the detoxified E. coli Heat-Labile Toxin (LTAK63), providing increased protection in mouse models and reduced lung pathology. Here, using systems biology and RNA sequencing of lung tissues in a murine model, we uncover the molecular mechanisms underlying rBCG-LTAK63’s increased protection. Immunization triggered early activation of cAMP-related pathways, leading to hypoxia, autophagy, and circadian rhythm gene regulation. These processes were associated with an enhanced innate immunity and promoted long-lasting Th1/Th17 adaptive responses. Upon challenge, mice immunized with rBCG-LTAK63 exhibited an earlier onset of interferon-gamma response, reduced bacterial burden, and improved lung histopathology. Notably, circadian rhythm regulation was directly linked to a controlled inflammatory response and reduced migration of infection-susceptible cells, resulting in decreased immunopathology. Our findings demonstrate that rBCG-LTAK63 orchestrates protection through the integration of metabolic and temporal immune pathways. This work provides mechanistic insights into how rational vaccine design can reprogram host immunity to enhance protection and reduce pathology, supporting rBCG-LTAK63 as a promising next-generation TB vaccine candidate.